OP0246-PARE Patients and Researchers Sometimes Think Alike: Patient Involvement in the Development of Quality Indicators for Osteoarthritis Care. (10th June 2014) - Blackburn, S.J.; Østerås, N.; Hagen, K.B.; Edwards, J.J.; Jordan, K.P.; Higginbottom, A.; Dziedzic, K.S.
Abstract : Background: People with osteoarthritis (OA) desire high quality care, support and information about OA. Quality indicators (QI) can set minimum standards of quality of care for OA. Following a literature review, researchers in the Musculoskeletal Pain in Ullensaker (MUST) study, Norway developed a patient questionnaire about the OA QIs reported by patients. This was reviewed by patient research partners and validated for Norwegian OA care (Østerås et al, 2013). At the same time, the Managing Osteoarthritis in Consultations (MOSAICS) study involved research users to develop a patient questionnaire about the OA QIs reported by patients for UK primary care. Objectives: We report on 1) the development of the MOSAICS OA-QI questionnaire; and 2) the comparison of the content of both OA-QI questionnaires. Methods: Members of an OA patient and public involvement (PPI) group at Keele University, UK were invited to meetings with researchers. From a list of OA-QIs considered suitable for primary care, which were identified by a systematic review (Edwards et al, 2013), PPI members discussed how relevant the OA-QIs are from a patient perspective and then each person chose their five most important. PPI members suggested wording and ways of answering for a draft MOSAICS OA-QI questionnaire. The PPI group then commented on the draft questionnaire and how it compared with the MUST OA-QI questionnaire. Results: PPI members (5 males, 7 females; aged 52-80 years) attended up to five meetings. Of 30 QIs initially identified, PPI members chose 20 as important for inclusion in a questionnaire. These covered pain self-management, medication use and side effects, daily activities, information about OA, quality of life and level of support. PPI members then helped to develop the wording of 14 items and ways of answering the items for the MOSAICS OA-QI questionnaire (some similar QIs were combined into single items). In comparison, the MUST QI questionnaire contained 17 items, but the ways of answering were the same. PPI members commented that both questionnaires contained the same or similar QIs. They felt that all of the MUST OA-QIs were important, though some of the translated Norwegian words were not suitable for OA patients in the UK. Conclusions: PPI members and researchers can agree on the important QIs for OA care. The UK PPI group produced quality indicators consistent with those chosen by researchers for Norwegian OA care. PPI in MOSAICS ensured that the OA-QIs were relevant and refined the item wording. The development of two OA-QIs questionnaires was a coincidence but it has provided a unique opportunity to compare QIs across European countries. This allows researchers to test how commonplace OA-QIs are in different populations and future research has been funded by EULAR to investigate this. References: Edwards J et al. Quality indicators for the primary care of osteoarthritis: a systematic review. Ann of the Rheum Dis 2013 (Published online first: 27 Nov 2013) Østerås N et al. Patient-reported quality of care for osteoarthritis: development and testing of the osteoarthritis quality indicator questionnaire. Arthritis Care Res 2013;65:1043-51 Acknowledgements: This presentation presents independent research funded by the National Institute for Health Research (NIHR) under its Programme Grants for Applied Research Programme (Grant Reference Number: RP-PG-0407-10386). The views expressed are those of the author(s) and not necessarily those of the NHS, the NIHR or the Department of Health. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2115